PENANGANAN PELANGGARAN MONEY POLITICS PADA PENYELENGGARAAN PEMILIHAN GUBERNUR, BUPATI DAN WALIKOTA TAHUN 2015 OLEH BAWASLU RI - Firdaus, Sunny Ummul; Pertiwi, Hana Ayu (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2017)
The election of the head of a region is the selection process to replace or maintain a political office the Governor and Deputy Governor, Governor and Deputy Governors as well as the Mayor and Deputy Mayor. the handling of an alleged violation of the election conducted by the supervisor of elections in accordance with the locus delicti and Bawaslu RI as Election Supervisors in the Agency's handling of an alleged violation of the election which took place on the Organization of the Elections of Governors, Regents and mayors of the 2015 election Watchdog that is has the authority to deal with alleged violations of the election. The supervision of the supervisor of elections to produce the data of supervision violation, namely an alleged violation of the crime of election money politics as much as unfinished report 929 of the total Reports received reports of 1090 as much, it is a problem for Election Supervisors in handling Infringement so that the handling of the 2015 election has not been going well, by examining the data evaluation results of organizing Elections by 2015, knowable constraints that encourage the emergence of problems and of any obstacle , the author offers some legal solutions in addressing problems in the handling of the alleged infringement.